Innovation, Competency and Public Satisfaction in Indonesia’s Emergency Medical Services: A Study of Semarang’s “Ambulan Hebat” - Mulajaya, R. Permadi; Christiani, Charis; Putera, Roni Ekha (Universitas Padjadjaran, 2026)
This study examines the effects of public service innovation and frontline employee performance competency on public satisfaction with Semarang’s “Ambulance Hebat” emergency service in Indonesia. The study situates itself within ongoing administrative reform efforts and the growing public demand for inclusive and responsive healthcare. A quantitative design was employed using survey data from 70 respondents associated with the Ambulance Hebat service at the Semarang Health Office. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess both the measurement and structural models. The measurement model demonstrates satisfactory reliability and convergent validity for the constructs of public service innovation, performance competency, and public satisfaction, while variance inflation factor (VIF) values indicate no multicollinearity concerns. Structural results indicate that public service innovation has a moderate, statistically significant effect on public satisfaction, whereas performance competency has a smaller yet significant effect. Together, these predictors explain 58.1% of the variance in public satisfaction, and the model exhibits strong predictive relevance. Substantively, publics respond positively to tangible innovations in service design and delivery and perceive the program’s technical and interpersonal competencies as credible markers of service quality. The findings suggest sustaining satisfaction in emergency healthcare requires complementary strategies: continuous refinement of service innovations alongside systematic investments in frontline capability and training, communication enhancement and performance management.